Efeitos dos recobrimentos de mucilagem de juá (Ziziphus joazeiro Mart.) no abacaxi (Ananas comosus L.) minimamente processado - Silva, Ricácia de Sousa (2021)
Pineapple is one of the main tropical fruits grown worldwide. Among the commercialized varieties Smooth Cayenne is one of the predominant in the Brazilian market. Pineapple is appreciated by its flavor, appearance, and nutritional composition standing out as source of vitamin C, phenolic compounds, minerals, and vitamin A. In the form of fresh-cut product pineapple becomes more convenient than whole fruit. However, minimal processing reduces its shelf life and time to market and the use of edible coatings mucilage-based can be effective in reducing these damage. Juá from Caatinga contains a mucilage still little explored and previous studies demonstrated the potential for obtaining and using of this mucilage for food purposes. Nonetheless, still there is no studies using juá mucilage in edible coatings to maintain the quality of fresh-cut pineapple, what boosted the development of this research. Thus, this work had as objective to evaluate the influence of edible coatings juá mucilagebased in the quality of fresh-cut Smooth Cayenne pineapple. The juá mucilage was extracted in microwave and resulting precipitate was used for obtain a juá phenolic extract. Pineapples were subjected to minimal processing followed of the application of coatings by immersion technique using four treatments: control - distilled water (T1), juá mucilage (T2), juá mucilage + juá phenolic extract (T3), and juá mucilage + gum arabic using the layer-by-layer technique (T4). After, the pineapples were packed and stored during 9 days at 5 ± 1 °C. The evaluation of the quality of pineapples was performed through physical-chemical methods of weight loss, firmness, instrumental color, acidity, pH, total soluble solids, and ascorbic acid. The activity of peroxidase and polyphenoloxidase, profile of sugars, organic acids, and phenolic compounds were determined. The antioxidant activity was analyzed by DPPH, ORAC and FRAP assays. Analysis of variance (ANOVA), Tukey test and polynomial regression analysis were used for statistical analysis of the results. T2 had the lowest browning index, lower increase in soluble solids and simple sugars and greater FRAP (138.19 μmol/Trolox) e ORAC (538.06 μmol/Trolox) after 9 days of storage. The antioxidant action of juá phenolics added to the coating (T3) reduced peroxidase activity and formed a coating more firmer able to maintain the acidity, organic acids and phenolic compounds in pineapples. T2 and T3 treatments reduced the action of polyphenoloxidase and had the lowest pH. Layer-by-layer technique (T4) reduced weight loss, ascorbic acid degradation and provided greater DPPH radical neutralization activity (116.81 μmol/Trolox). Just like T4, T3 reduced the loss of firmness. All treatments delayed the decrease in whiteness and luminosity. Thus, was concluded that edible coatings juá mucilage-based and mucilage added with phenolic extract of juá have application potential to preserve quality and extend the shelf life of fresh-cut pineapple during 9 days of storage.